Peculiarities of gas-discharge luminescence of biological fluid from the achilles tendon in the late postmortem period - Povstyanyi, V. A.; Pesotskaya, L. A.; Glukhova, N. V.; Yevdokimenko, N. M.; Nikogosyan, L. R.; Koshelnik, Ye. L. (Journal of Education, Health and Sport, 2017)
The work was explored the kinetics of the changes in the components of the liquid from Achilles tendon, that occur in the tissue of the Achilles tendon as a result of processes of autolysis, within 2-3, 4-6, 7-9 and 10-20 days post-mortem period. The gas-discharge luminescence of biological fluid was studied on x-ray film. More than 50 droplets for each group were investigated. The histograms were analyzed the brightness of the amplitude peaks in the 7 sub-bands of each sample liquid. Median was determined of the obtained sample values and the difference between the medians of the number of pixels in the current sub-band brightness with of the previous. The ratio of the differences of the subsequent diapason the previous was established, to assess the rate of change of luminescence intensity. The differences of GR-glow liquid of the Achilles tendon in the compared groups was revealed depending on the time of death. It was established that to use histograms to detect differences and peculiarities in the luminescence of biological objects, could have practical value for solving the question of the time of death. It is appropriate to further study of changes in the content of the various components of corpses’ tissues in conjunction with the biophysical studies. This can provide valuable scientific and practical material for the needs of pathomorphology and forensic medicine.